Penerapan Metode Two Sided Side Match Untuk Penyisipan Gambar Pada File Audio - Lase, Fiderman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Message data security at this time is very important to do security techniques, because of the increasing number of users of communication media technology that is increasing so that other parties can find out the contents of the message. Steganography technique is a technique that can be used to insert picture messages in audio files. The Two Sided Side Match method is a Steganography method that uses two sides of the pixel value, namely the top side and the top right side. To determine how many binary images to insert into a pixel. This Steganography method is also the art of hiding secret messages with a technique that does not arouse the suspicion of the other party, so that the message can only be known by the sender and recipient of the message which was built using the Microsoft Visual Studio 2010 programming language. important messages or secret messages because the steganography technique hides important messages on certain objects. In this very efficient steganography technique, it is used to hide messages without reducing the quality of the inserted message object